Letter to the Editor Regarding "Hypertension Awareness, Treatment, and Control in Mexico: An Opportunistic Medical Student-led Blood Pressure Screening Campaign - A Cross-Sectional Study" - Patricio Garcia-Espinosa (University Library System, University of Pittsburgh, 2021)
Awareness campaigns on the consequences of chronic degenerative diseases are cost-effective strategies to educate the general population; these in turn can be carried out by groups of medical students that allow their rapid dissemination in different media as has been shown with the current pandemic; it is necessary to educate the general population on the relationship between systemic arterial hypertension and ischemic and hemorrhagic stroke. Student groups focused on these diseases, such as the Group of Students Against Neurological Diseases (GECEN) of the School of Medicine of the Autonomous University of Nuevo Leon (UANL) are an area of opportunity for community education.